If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 = 3x + 6 Reorder the terms: 3 + x = 3x + 6 Reorder the terms: 3 + x = 6 + 3x Solving 3 + x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + x + -3x = 6 + 3x + -3x Combine like terms: x + -3x = -2x 3 + -2x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + -2x = 6 + 0 3 + -2x = 6 Add '-3' to each side of the equation. 3 + -3 + -2x = 6 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 6 + -3 -2x = 6 + -3 Combine like terms: 6 + -3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5
| 53=3x+8 | | 7x+-140=56 | | 18x+9=9x+18 | | 53-5=x | | 8+7z/11 | | 5(2x+3)+4(x-7)= | | (3x+2)+11=(22-x)+11 | | -3(-4-2n)=36 | | G=5/2-21 | | 5(.75)-2y=-9 | | 2.99=19.99+1.99 | | 180-148= | | -22=6y+2(y+5) | | -13x+12-11+15x=4(3x-7)-1 | | 4/7x=3/14 | | 2.99=1999+199 | | 1/2z+7=-3 | | 4x+3x-140=56 | | 7z+11-4-1+1=31 | | 2m-5/9 | | (3c-3)(4c+8)= | | 8w+6=-2(w-7) | | lx+3l=3x+6 | | 3(x+5)-2x=15 | | 6x-77+2x=43 | | -16/9=-8u | | 7x-2(1+3x)=2 | | 18+5w=3w-10 | | 5y-3/5=4/3 | | -(3v+4)=6v-3(3v+2) | | 77+4x=43 | | -2x(3x+4)+y=0 |